The potential of ribonucleotide reductase M2 as a novel prognostic maker and therapeutic target to inhibit medulloblastoma proliferation, migration, and invasiveness - Xuanxuan Wu; Pan Gou; Chencheng Fang; Yudong Zhou; Lusheng Li; Xuan Zhai; Ping Liang (Wiley, 2024)
Abstract The crucial role of ribonucleotide reductase M2 (RRM2) enzyme in cancer occurrence and progression has been well‐established, but its specific function and significance in medulloblastoma (MB) remains largely unknown. First, we conducted a bioinformatics analysis of public genomic databases and observed highly expressed RRM2 in MB and an association of high RRM2 expression with adverse outcomes. In addition, by collecting clinical MB specimens for polymerase chain reaction (PCR), western blotting (WB), and immunohistochemistry (IHC), RRM2 was confirmed to be highly expressed in tumor tissues. Furthermore, immunohistochemical analysis linked adverse prognosis to high RRM2 expression. Moreover, knocking down RRM2 significantly inhibited MB cell proliferation, migration, and invasion in vitro. This report is the first to demonstrate the oncogenic role of RRM2 in MB, associated with adverse patient outcomes. Knocking down RRM2 contributes to weakened proliferating, migrating, and invading potentials of MB cells. RRM2 is expected to be a novel prognostic biomarker and therapeutic target for MB.